Anthropocentrism and Environmental Change in Selected Raghini Upadhaya’s Paintings - Bhatta, Sujata (Pragnya Sarathi प्रज्ञा-सारथि, 2024)
Human beings and Nature are interrelated. Nature influences and is influenced by human beings. By analyzing paintings of Ragini Upadhyay Grela from her collection "Nature speaks" this paper will try to find out the amalgamated relationship between human beings and nature. The paper firmly depends upon two paintings from Upadhyay’s collection "Nature speaks". The artist has given the quotation in her collection; "Protect nature to save our future", by analyzing her technique, style as well as colour combination to the paintings and their meaning. Similarly, it also analyzes her mythical concept to find out how anthropocentric activities are destroying nature and her paintings have become a kind of challenge for so-called intellectual and rational human beings. Moreover, this paper tries to explain the theme of Sustainable Development and Ecology in general and it concentrates on arts and creativity as resources for sustainability in specific. In this regard, the paper offers insights into the role of arts to illuminate the issues of sustainability. Following the arts-based inquiry, the paper critiques the anthropocentric activities for advocating sustainability.